2022
DOI: 10.1177/20416695221127325
|View full text |Cite
|
Sign up to set email alerts
|

Crossmodal correspondences between basic tastes and visual design features: A narrative historical review

Abstract: People tend to associate abstract visual features with basic taste qualities. This narrative historical review critically evaluates the literature on these associations, often referred to as crossmodal correspondences, between basic tastes and visual design features such as color hue and shape curvilinearity. The patterns, discrepancies, and evolution in the development of the research are highlighted while the mappings that have been reported to date are summarized. The review also reflects on issues of cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 124 publications
0
8
0
Order By: Relevance
“…Following this idea, experimental psychologist Charles Spence addressed the topic by questioning whether turning off the lights really make the food and drink taste better in normal sighted subjects, and he showed that diners often found it difficult to distinguish between flavours in the absence of any visual cues [ 45 , 46 ]. In fact, colour-taste and shape-taste crossmodal correspondences according to cultural context are well documented [ 47 ]. Regarding this topic, Weismann and collaborators investigated typical patterns of cortical activity by fMRI studies.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Following this idea, experimental psychologist Charles Spence addressed the topic by questioning whether turning off the lights really make the food and drink taste better in normal sighted subjects, and he showed that diners often found it difficult to distinguish between flavours in the absence of any visual cues [ 45 , 46 ]. In fact, colour-taste and shape-taste crossmodal correspondences according to cultural context are well documented [ 47 ]. Regarding this topic, Weismann and collaborators investigated typical patterns of cortical activity by fMRI studies.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Plenty of literature has provided evidence that shapes’ curvilinearity (roundedness and angularity) may have consistent cross-modal correspondences with other sensory attributes ( Spence, 2011 ; Spence and Ngo, 2012 ; Ghoshal et al, 2016 ; Lee and Spence, 2022 ). For instance, people associate curved shapes with a sweet taste, quiet or calm sound, vanilla smell, green color, smooth texture, relieved emotion, female gender, and wide-vowel names; while they associate angular shapes with sour taste, loud or dynamic sound, spicy or citrus smell, red color, rough texture, excited or surprise emotion, male gender, and narrow-vowel names ( Blazhenkova and Kumar, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, people associate curved shapes with a sweet taste, quiet or calm sound, vanilla smell, green color, smooth texture, relieved emotion, female gender, and wide-vowel names; while they associate angular shapes with sour taste, loud or dynamic sound, spicy or citrus smell, red color, rough texture, excited or surprise emotion, male gender, and narrow-vowel names ( Blazhenkova and Kumar, 2017 ). Different hypotheses have been proposed for the cross-modal correspondence effect ( Lee and Spence, 2022 ). One is the statistical account, which means the internalization of the multisensory statistics of the environment.…”
Section: Introductionmentioning
confidence: 99%
“…By using the documented patterns of crossmodal correspondences between vision and taste (such as sweet being associated with pink and red) in product packaging and visual presentation of food and drinks, research shows that specific visual features can alter people’s taste expectations, and sometimes also their taste and flavor experiences (Velasco, Hyndman, & Spence, 2018; Velasco, Michel, et al, 2016; see B. P. Lee & Spence, 2022; Spence et al, 2015).…”
mentioning
confidence: 99%
“…By using the documented patterns of crossmodal correspondences between vision and taste (such as sweet being associated with pink and red) in product packaging and visual presentation of food and drinks, research shows that specific visual features can alter people's taste expectations, and sometimes also their taste and flavor experiences (Velasco, Hyndman, & Spence, 2018;Velasco, Michel, et al, 2016; see B. P. Lee & Spence, 2022;Spence et al, 2015). Thus far, visual features such as color hue (Spence, 2019), curvilinearity (Velasco, Woods, et al, 2016), symmetry (Turoman et al, 2018), and other nonverbal visual cues (e.g., visual texture;Barbosa Escobar et al, 2022) have been shown to give rise to specific taste expectations.…”
mentioning
confidence: 99%